2017
DOI: 10.4238/gmr16029543
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism E23K (rs5219) in the KCNJ11 gene in Euro-Brazilian subjects with type 1 and 2 diabetes

Abstract: ABSTRACT. Insulin secretion is regulated by ATP-sensitive potassium channels (KATP). The potassium inwardly-rectifying channel, subfamily J, member 11 (KCNJ11) gene, located on chromosome 11p15.1, encodes the subunit Kir6.2 that forms the pore region of KATP channels in pancreatic β-cells. Among the single nucleotide polymorphisms (SNPs) associated with KCNJ11, the E23K polymorphism (rs5219) promotes a substitution (G > A) of a glutamic acid residue for lysine at position 23. The E23K SNP has been associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Qiu et al confirmed that the rs5219 polymorphism of KCNJ11 predisposes to T2DM, mostly in Caucasians [ 93 ]. On the other hand, Souza et al demonstrated that the same polymorphism E23K (rs5219) was not associated with type 1 or 2 diabetes mellitus in Euro-Brazilian subjects [ 94 ]. A meta-analysis performed by Qin, L.J.…”
Section: Role Of Ion Channels In the Pathophysiological Continuum mentioning
confidence: 99%
“…Qiu et al confirmed that the rs5219 polymorphism of KCNJ11 predisposes to T2DM, mostly in Caucasians [ 93 ]. On the other hand, Souza et al demonstrated that the same polymorphism E23K (rs5219) was not associated with type 1 or 2 diabetes mellitus in Euro-Brazilian subjects [ 94 ]. A meta-analysis performed by Qin, L.J.…”
Section: Role Of Ion Channels In the Pathophysiological Continuum mentioning
confidence: 99%
“…These associations were not significant in patients with spinal onset, which implies a role for the K ATP channel in tissue susceptibility to cell loss and ALS pathogenesis. Three of the bulbar-onset ALS patients with rs4148646 G/G and rs5219 [29,[58][59][60]. The association of these two variants with a longer survival time in bulbar ALS patients may be related to the role of the K ATP channel in the control of microglia-mediated inflammatory processes.…”
Section: Discussionmentioning
confidence: 93%
“….5) showed that only HbAlc had a significant difference (p value =0.01). Leptin (p value = 0.95), C-peptide (p value = 0.47), cystatin C (p value = 0.86), insulin (p value = 0.65) and HOMA (p value = 0.65) were not statistically significant Souza et al, (2017). found that HbAlc medians were significantly higher in T2DM patients than the control group (p value = 0.001).…”
mentioning
confidence: 87%